Video over IP : a practical guide to technology and applications - Simpson, Wes (Focal Press media technology professional., 2006)
Video Over IP gives you everything you need to know to choose from among the many ways of transferring your video over a network. The information is presented in an easy to read format, with comparison charts provided to help you understand the benefits and drawbacks of different technologies for a variety of practical applications.Readers who have a background in either video or networking will benefit from tutorials in both areas and the breadth of coverage that this book provides. Real-life application examples give readers successful examples of a variety o.